UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MANGGA ARUM MANIS (Mangifera indica L. ‘Arumanis’) TERHADAP Staphylococcus aureus - Cinta Alya; Astriani Natalia Br Ginting; Daimah Wirdatus Sanaun Harahap (Jurnal Buana Farma, 2026)
The increasing prevalence of bacterial resistance to antibiotics has encouraged the exploration of natural products as alternative antimicrobial agents. This study aimed to evaluate the inhibitory potential of the ethanolic extract of ‘Arumanis’ mango leaves (Mangifera indica L. ‘Arumanis’) against Staphylococcus aureus ATCC 25923. The research was conducted using a laboratory experimental design including plant identification, preparation of simplicia, extraction by maceration with 96% ethanol, phytochemical screening, and antibacterial activity testing using the disk diffusion method. The extract was tested at concentrations of 5%, 10%, and 15% (50–150 mg/mL), with three replications (n=3) for each treatment and control group. The inhibition zones were measured including the 6 mm disk diameter and analyzed descriptively as mean ± standard deviation. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and triterpenoids. The antibacterial assay showed inhibition zone diameters of 3.00 ± 2.12 mm (5%), 4.38 ± 2.51 mm (10%), and 6.13 ± 2.63 mm (15%), while the positive control chloramphenicol (30 µg/disk) produced a 21.43 ± 0.06 mm inhibition zone and the negative control (10% DMSO) showed no inhibitory effect. Although inhibition zones were observed at all concentrations, the diameters were relatively small compared to the standard antibiotic. Therefore, the ethanolic extract of M. indica ‘Arumanis’ leaves demonstrates concentration-dependent inhibitory potential against S. aureus, but with limited antibacterial activity, indicating the need for further evaluation using dilution methods to determine the Minimum Inhibitory Concentration (MIC).